Guinea : First Review Under the Three-Year Arrangement Under the Extended Credit Facility, Financing Assurances Review, Request for a Waiver of Nonobservance of a Performance Criterion and Request for Modification of Performance Criteria-Staff Report; Informational Annex; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Guinea.: Request for a Waiver of Nonobservance of a Performance Criterion and Request for Modification of Performance Criteria-Staff Report; Informational Annex; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Guinea. (IMF Staff Country Reports; Country Report, 2012)
Guinea is making good progress in recovering from a long period of social unrest and military rule. Macroeconomic imbalances have been reduced, major structural reforms are under way, and long-neglected infrastructure is being rebuilt. However, the political transition process is still incomplete, with parliamentary elections having been delayed, and social tensions persist. Guinea remains vulnerable to developments in international markets, but risks are mitigated by long-term mining contracts; the key food import is rice, where recent international price increases have been modest and where agricultural reforms seek to boost domestic production.